Therapeutic hypothermia as a treatment strategy for neonates born in asphyxia - a review of the current state of knowledge - Koryszko, Klaudia; Pokrywka, Natalia; Suwała, Dawid; Polak, Marcelina; Hetnar, Paulina; Kiper, Sebastian; Fortuna, Milena; Toczek, Sławomir; Tomala, Magdalena; Jastrowicz-Chęć, Katarzyna (Quality in Sport, 2025)
Purpose: The aim of this review is to synthesize current scientific evidence on the efficacy, indications, limitations and controversies surrounding HT in asphyxiated neonates. Materials and research methods: The article is based on an analysis of research available on PubMed , Cochrane and Scopus. A literature review was conducted using following keywords such as “therapeutic hypothermia”, “neonatal asphyxia”, “hypoxic-ischemic encephalopathy”, “newborns” and “neuroprotection”. Inclusion criteria: studies on newborns ≥ 36 weeks of fetal life, clinical trials, systematic reviews, meta-analyses. Results: Therapeutic hypothermia (HT) reduces the risk of death and severe disability in term infants (≥36 weeks) with moderate/severe HIE, supported by meta-analyses (RR 0.75 for death, RR 0.77 for disability) and long-term benefits. Evidence is lacking for preterm infants and mild HIE. Side effects (e.g., bradycardia, hypotension) are usually transient. In developing countries (HELIX trial), HT may lack benefit or even increase mortality—highlighting the need for tailored approaches. Conclusion: Therapeutic hypothermia remains the most effective neuroprotective intervention for term and near-term neonates with moderate to severe hypoxic-ischemic encephalopathy. Despite its proven benefits, further research is needed to evaluate its safety and efficacy in preterm infants, mild HIE cases, and low-resource settings.